2020
DOI: 10.1101/2020.08.14.20174490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection, prevalence, and duration of humoral responses to SARS-CoV-2 under conditions of limited population exposure

Abstract: We conducted an extensive serological study to quantify population-level exposure and define correlates of immunity against SARS-CoV-2. We found that relative to mild COVID-19 cases, individuals with severe disease exhibited elevated authentic virus-neutralizing titers and antibody levels against nucleocapsid (N) and the receptor binding domain (RBD) and the S2 region of spike protein. Unlike disease severity, age and sex played lesser roles in serological responses. All cases, including asymptomatic individua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
33
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 62 publications
10
33
0
3
Order By: Relevance
“…Such observations are also supported by a number of additional studies that also measured a decline of IgG antibodies after several weeks PSO (44,131). However, most groups have demonstrated that IgG levels against SARS-CoV-2 remained relatively stable within a 3 to 5 month observation period PSO (43,124,(130)(131)(132)(133)(134)(135).…”
Section: Dynamics Of the Antibody-mediated Immune Response To Sars-cov-2mentioning
confidence: 69%
“…Such observations are also supported by a number of additional studies that also measured a decline of IgG antibodies after several weeks PSO (44,131). However, most groups have demonstrated that IgG levels against SARS-CoV-2 remained relatively stable within a 3 to 5 month observation period PSO (43,124,(130)(131)(132)(133)(134)(135).…”
Section: Dynamics Of the Antibody-mediated Immune Response To Sars-cov-2mentioning
confidence: 69%
“…Symptoms typically develop within 6 days after exposure but may develop as early as 2 days or as late as 14 days [1,33]. More than 95% of symptomatic COVID patients have positive antibody (IgG) titres within 17-19 days of symptom onset, and those antibodies remain elevated over a sustained period [34][35][36][37]. The mean time interval from symptom onset to death is 15 days for ages 18-64 and 12 days for ages 65 + , with interquartile ranges of 9-24 days and 7-19 days, respectively, while the mean interval from date of death to the reporting of that person's death is about 7 days with an IQR of 2-19 days; thus, the upper bound of the 95% confidence interval between symptom onset and reporting of fatalities is about 6 weeks (41 days) [38].…”
Section: Measurement Of Fatalitiesmentioning
confidence: 99%
“…So far, data on long-term immunity to SARS-CoV-2 are lacking. Available reports, up to three months after COVID-19 are partially con icting, but overall point towards a decrease and even loss of SARS-CoV-2-speci c antibody responses (4)(5)(6)(7)(8) and thus raise concerns regarding longterm humoral immunity. In SARS-CoV-1, T cell immunity was identi ed as important determinant for recovery and long-term protection (9-12), with long-lasting memory T cell responses detected in convalescents even 17 years after infection (13).…”
Section: Main Textmentioning
confidence: 99%